EFEKTIVITAS E-BOOK INTERKATIF BERBASIS CANVA UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK SD PADA PEMBELAJARAN IPA - Bariroh; Sudarmin; Sri Wardani; Wahyu Lestari; Bambang Subali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Critical thinking is part of the skills that learners must have in the 21st century. Critical thinking skills need to be mastered by students so that students have the provision to face global challenges in the increasingly sophisticated digitalisation era and to be able to solve problems in everyday life. Students' critical thinking skills are expected to be familiarised through learning activities at school. The expected conditions are different from the conditions that occur in the field, namely the skills of students to think critically are still low. This is a problem that we need to overcome. The low skill of students to think critically is because the learning process is still conventional and does not utilise learning materials that can train students to practice critical thinking. The use of technology can be used by teachers to create interactive learning materials such as interactive e-books assisted by Canva so that the learning process becomes meaningful. A meaningful learning process provides opportunities for students to hone critical thinking skills. This study aims to describe the effectiveness of interactive e-books assisted by Canva to improve students' critical thinking skills in science learning. The research method used is a literature study on journal articles related to e-books and critical thinking skills. The data analysis technique used is qualitative analysis. The results of the literature review conducted show that the use of e-books is effective in science subjects to improve the critical thinking skills of elementary school students